Charged and neutral kaon production in electron-positron annihilation - Ivashyn, S.A.; Korchin, A.Yu. (Вопросы атомной науки и техники, 2007)
A model for description of electromagnetic form factors of the charged and neutral kaons in the energy region √s ~ 1-2 GeV is presented. Our approach is based on extended vector-meson-dominance model. It accounts for dependence of photon-meson vertices on the invariant energy and includes self-energy contribution to vector-meson propagators. Interaction vertices follow from Lagrangian of Chiral Perturbation Theory (ChPT) with explicit vector-meson degrees of freedom. The form factors, calculated without fitting parameters, are in a good agreement with experiment for space-like and time-like photon momenta. In addition we have calculated contribution of the KK channel to the muon anomalous magnetic moment.